Ancient mosaic pavements : themes, issues, and trends : selected studies - Hachlili, Rachel. (Biblical Studies, Ancient Near East and Early Christianity E-Books Online, Collection 2009, ISBN: 9789004222724., 2009)
This publication is engaged in issues, trends, and themes depicted on mosaic pavements discovered in Israel, the Gaza Strip and Petra (the provinces of ancient Palaestina Prima, Secunda and Tertia) with comparable floors in Jordan (Arabia). The majority of the mosaic pavements discussed in this study are dated to the 4th-8th centuries CE. Mosaic pavements were the normal medium for decorating the floors of synagogues, churches, monasteries, and chapels, as well as public and private buildings. Inscriptions found on many of the pavements commemorate the donors, refer to the artists, and sometimes date the mosaics. The ornamentation of the mosaics in this region is remarkable, rich, and varied in its themes and provides many insights into the contemporary artistic and social cultures.